2019
DOI: 10.3808/jeil.201900020
|View full text |Cite
|
Sign up to set email alerts
|

Perspective for Emission and Control of Nitrous Gas in Biological Wastewater Treatment

Abstract: Being the third most significant anthropogenic greenhouse gas, nitrous gas (N2O) has 300-fold stronger effect than carbon dioxide (CO2) and 4 ~ 30-fold stronger effect than methane (CH4). In this study, the main sources and mechanisms of N2O emission from biological wastewater treatment were reviewed, and the possible mitigation strategies were discussed. Parameters including dissolved oxygen, temperature, pH, organic carbon, and nitrite concentration have influences on the emission of N2O. The possible mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…The associated effects on the environment include noise and air pollution, land occupancy, and traffic accidents. Urban dispersion uses up land that would otherwise be available for ecological uses, while the excessive energy consumption leads to air pollution, exhaustion of non-renewable energy, and gas emissions, which ultimately contribute to climate change (Anderson et al, 1996;Wu and Xia, 2019;Chen et al, 2020;Liu et al, 2020). Ewing and Rong (2008) conducted a study investigating the relationship between the choice of housing type and urban form, and found that multifamily housing is seven time less popular in dispersed areas than in compact areas.…”
Section: Dispersed Citymentioning
confidence: 99%
“…The associated effects on the environment include noise and air pollution, land occupancy, and traffic accidents. Urban dispersion uses up land that would otherwise be available for ecological uses, while the excessive energy consumption leads to air pollution, exhaustion of non-renewable energy, and gas emissions, which ultimately contribute to climate change (Anderson et al, 1996;Wu and Xia, 2019;Chen et al, 2020;Liu et al, 2020). Ewing and Rong (2008) conducted a study investigating the relationship between the choice of housing type and urban form, and found that multifamily housing is seven time less popular in dispersed areas than in compact areas.…”
Section: Dispersed Citymentioning
confidence: 99%